School knowledge and everyday knowledge: why the binary conceptualization? - Mutemeri, Judith (2016)
The aim of the paper is to illuminate the underlining reasons for the binary conceptualization of school knowledge and everyday knowledge. The historical and philosophical lens will be used as analytical tools for this discussion. The main argument of this paper is that the binary conceptualization of school knowledge and everyday knowledge is a social construct with latent functions where the colonizer's aim was to unfit the colonized for their habitation in order to maintain dependence and therefore ensure a continued supply of labour for their business establishments. Using Critical Pedagogy Theory that links education with the analysis of politics and economy; the paper also provides theoretical analysis on how learners and teachers are subjected to and are subjects of schooling in an effort to show how the binary conceptualization of school knowledge and everyday knowledge have been sustained and maintained. Last, the paper suggests Shor's and Freire's (1987) situated pedagogy which uses learner's everyday knowledge as foundation for the acquisition of school knowledge, and looks at the implication of the duality of the conceptualization of school knowledge and everyday knowledge for teacher education for readers introspection.